ANALISA PENGEMBALIAN MODAL PADA PETERNAKAN AYAM PETELUR RAJIMAN DI TANJUNG BINTANG - Yudiana Sari (Industrika : Jurnal Ilmiah Teknik Industri, 2017)
This study using the object research is breeder chicken egg layer Surajiman, Tanjung Bintang. The effort farms chicken egg layer Surajiman, Tanjung Bintang. Was founded by Mr. Surajiman in 2016 in the Village Serdang IIIA, Tanjung Bintang. This is built on a farm land with a land area of 200 m2, with the number of cattle chicken as much as 600 tail. In this study data taken still 600 tail. In doing this business Mr. Surajiman still managed myself because the number of chicken in pet still relative a little. If a farm knowing stages where at first chicken only number 600 tail. On the life-cycle of certain before the production of the egg declined, then it can be added to the become more, in addition should also divide the chicken in some period of the age of chicken in order to maintain the cycle of the age of chicken so can improve the quality of the egg results his production. With knowing the cycle of chicken, it will make a farm become more advanced in the production of peck at her eggs and increased profits that in the future. Key Word : The point behind his back in the capital.